Clustering Analysis on Financial Literacy, Digital Literacy, and Digital Financial Literacy of Emerging Adults (Gen Z) Investors in Rural East Java - Amalina Maryam Zakiyyah (Universitas Muhammadiyah Jember, 2025)
Financial literacy, digital information literacy, and digital financial literacy are essential competencies for young adults in rural Jawa to navigate dynamic economic and technological challenges. This study aims to explore literacy profiles among young adults using cluster analysis. A quantitative method was employed through a survey of 135 respondents from rural areas, followed by cluster analysis to identify distinctive literacy patterns The results reveal five distinct literacy profile classes with unique characteristics. The